Subject analysis of the providing mechanism of rights and freedoms of man and citizen - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article investigates the questions of definition and classifications of subjects of providing of rights and freedoms of man and citizen and also focuses attention on the consequences of their powers to ensure the rights and freedoms of man and citizens.